2017
DOI: 10.1016/j.toxrep.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Vinblastine, an anticancer drug, causes constipation and oxidative stress as well as others disruptions in intestinal tract in rat

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
(26 reference statements)
3
24
0
Order By: Relevance
“…This mechanism was evaluated by lipid peroxidation, protein oxidation, and damaging actions on sulfhydryl groups. Disorders in the normal redox state of cells can induce toxic activities through the generation of free radical reactive oxygen species that induce cell injury and alter these cellular macromolecules [14]. These obtained results are in agreement with those found by Li et al [15] who revealed that the level of MDA augmented in constipated rats.…”
Section: Oxidative Stress and Constipationsupporting
confidence: 91%
“…This mechanism was evaluated by lipid peroxidation, protein oxidation, and damaging actions on sulfhydryl groups. Disorders in the normal redox state of cells can induce toxic activities through the generation of free radical reactive oxygen species that induce cell injury and alter these cellular macromolecules [14]. These obtained results are in agreement with those found by Li et al [15] who revealed that the level of MDA augmented in constipated rats.…”
Section: Oxidative Stress and Constipationsupporting
confidence: 91%
“…Although hydrogen peroxide is still harmful to the body, CAT can degrade it into water. SOD and CAT will form into an oxidation resistant chain to remit the damage to the intestinal tract that is caused by constipation [31]. The results of our study indicate that LP-CQPC10 could effectively remit the reduced activity of Cu/Zn-SOD, Mn-SOD, and CAT caused by constipation.…”
Section: Discussionmentioning
confidence: 70%
“…Acute UG diagnosis was evaluated by different clinical signs, such as gastric juice volume, ulcer score and gastric pH. Colonic alterations were caused in vivo according to the method elucidated by Rtibi et al 18 Briey, animals were intoxicated with intravenous injection of vinblastine (2 mg kg À1 of body weight in a saline solution) for 7 days. Diagnosis of VINB injuries was conrmed by several signs, such as fecal pellet, wet fecal weight, dry fecal weight and water content.…”
Section: Animalsmentioning
confidence: 99%